2022
DOI: 10.1038/s41440-022-00986-1
|View full text |Cite
|
Sign up to set email alerts
|

Renalase: a novel regulator of cardiometabolic and renal diseases

Abstract: Renalase is a ~38 kDa flavin-adenine dinucleotide (FAD) domain-containing protein that can function as a cytokine and an anomerase. It is emerging as a novel regulator of cardiometabolic diseases. Expressed mainly in the kidneys, renalase has been reported to have a hypotensive effect and may control blood pressure through regulation of sympathetic tone. Furthermore, genetic variations in the renalase gene, such as a functional missense polymorphism (Glu37Asp), have implications in the cardiovascular and renal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 107 publications
0
5
0
Order By: Relevance
“…In addition to its link to Li response in BP (Amare et al 2023 ), serum renalase levels have been reported to be lower in patients with schizophrenia (SCZ) than in control individuals (Catak et al 2019 ), and Li response was previously shown to inversely associate with the genetic risk for SCZ (Amare et al 201 8). RNLS is thought to modulate blood pressure and cardiac function, and has been associated with metabolic and cardiovascular alterations as well as kidney disease (Vijayakumar & Mahapatra 2022 ), all of which are affected by Li. Similar are the cases of CSMD2 and GRIN2A , which are involved in the control of the complement cascade and N-methyl-D-aspartate (NMDA) receptor activity, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its link to Li response in BP (Amare et al 2023 ), serum renalase levels have been reported to be lower in patients with schizophrenia (SCZ) than in control individuals (Catak et al 2019 ), and Li response was previously shown to inversely associate with the genetic risk for SCZ (Amare et al 201 8). RNLS is thought to modulate blood pressure and cardiac function, and has been associated with metabolic and cardiovascular alterations as well as kidney disease (Vijayakumar & Mahapatra 2022 ), all of which are affected by Li. Similar are the cases of CSMD2 and GRIN2A , which are involved in the control of the complement cascade and N-methyl-D-aspartate (NMDA) receptor activity, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, RNL is a cytokine that modulates the mitogen-activated protein kinase pathway leading to cytoprotective, anti-inflammatory, and antiapoptotic effects [reviewed in 59 ]. According to current knowledge, RNL might modulate blood pressure in animals and humans by influencing catecholamine metabolism, renal dopamine secretion, and renal sympathetic innervation [ 19 , 59 , 60 ]. For instance, the renalase-knockout mice showed increased systolic and diastolic blood pressure and increased catecholamine concentrations compared to the wild-type animals despite normal renal function [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, RNL is investigated mainly in the context of chronic kidney, cardiovascular and oncologic diseases [ 60 ], while the possible associations with reproductive disturbances are poorly explored. However, abundant RNL expression has been described in rodent ovaries and adrenal glands [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, renalase can hinder inflammasome activation and the release of IL-1β [ 32 , 44 , 62 ]. Taken together, renalase favors significant cytoprotection related to inflammation, oxidative stress, and apoptosis [ 28 , 29 , 30 , 31 , 32 , 37 , 38 , 39 , 50 , 59 , 62 ], whereby recent research also discloses its potential in diverse cardiac [ 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ] and kidney pathologies [ 75 , 76 , 77 , 78 ] and in the pathophysiology of COVID-19 [ 79 , 80 ]. It will be captivating to conduct future scrutiny toward an excellent comprehension of renalase pleiotropy.…”
Section: The Molecular Signature Of Renalasementioning
confidence: 99%